Impact of timing of nintedanib initiation among patients newly diagnosed with idiopathic pulmonary fibrosis. (31st December 2022) - Singer, David; Bengtson, Lindsay G. S.; Conoscenti, Craig S.; Anderson, Amy J.; Brekke, Lee; Shetty, Sharash S.; de Andrade, Joao
Abstract: Aims: While nintedanib treatment has been shown to slow the progression of idiopathic pulmonary fibrosis (IPF) in patients across varying levels of lung function, the effect of treatment timing on outcomes has not been examined. We assessed hospitalization risk and medical costs among patients with IPF based on the timing of nintedanib initiation after IPF diagnosis. Materials and methods: This retrospective administrative claims study included data from 04/01/2014–09/30/2019 for patients aged ≥40 years who initiated nintedanib within 1 year of IPF diagnosis. Patients were assigned to study cohorts based on the time from IPF diagnosis to nintedanib initiation. All-cause hospitalization and all-cause medical costs were modeled using marginal structural models including inverse probability weights to adjust for both baseline and time-varying characteristics. Results: Of 11, 195 patients diagnosed with IPF during the identification period, 449 met the study selection criteria (mean age 72.3 years, 68% male, mean follow-up time 13.3 months). Adjusted hospitalization risk and medical costs both varied significantly by the timing of nintedanib initiation ( p < .001 and p = .020, respectively). Adjusted weighted hospitalization risk was higher among untreated vs. treated patients in months 2–3, months 4–6, and months 7–12 after diagnosis (hazard ratio [95% CI] 1.97 [1.09–3.56], p = .026; 2.62 [1.22–5.63], p = .014; and 5.57 [2.31–13.45], p < .001, respectively). Medical costs were 69% higher for patients initiating treatment in months 2–3 vs. month 1 (cost ratio [95% CI] 1.69 [1.20–2.38], p = .003). Limitations: Disease severity could not be assessed because clinical data were unavailable; however, proxies such as oxygen use were included to adjust for between-cohort differences in disease severity. Conclusions: Patients who initiate nintedanib promptly after IPF diagnosis may have reduced hospitalization risk and medical costs compared with those who start treatment later. Additional studies are warranted to improve understanding of the impact of prompt antifibrotic therapy on patient outcomes.